Max-Miner Method in Improving Food Sales Strategy - Furqan, Mhd; Sriani, Sriani; Ningsih, Siti Alus (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Competition in the corporate world is currently very intense, especially in the retail business sector, one of which is the retail food business. Building a minimarket retail business, provides staple foods that are unavoidable using information technology to support the smooth sales of these products. The use of this information technology has become a necessity in the retail minimarket business world whose aim is to provide maximum profits and minimal losses with promotions that must be done in terms of providing the best service in a retail minimarket that must use the best business strategy, but sometimes the retail minimarket manager constrained in determining the sales strategy. One of the factors is the difficulty of producing an analysis related to the products sold. Therefore we need an analysis of the application of data mining so that product sales at retail minimarkets are increasing and service to consumers is getting better. In this design data mining and algorithms are used, namely market basket analysis and Max-Miner. By applying the Max-Miner method in the data mining process for sales strategies at retail minimarkets, it will produce rule associations that will become product recommendations that will provide a decision in sales strategy for the mini market